Método para posicionamento estratégico sustentável no desenvolvimento de um novo produto - Lima, Rodrigo Costa de Souza (Universidade do Vale do Rio do Sinos, 2010)
Based on concepts of Sustainability, Life Cycle Assessment (LCA) and financial factors, this paper proposes an array of strategic positioning of product and a method for its implementation. The Sustainable Strategic Positioning Matrix (MPESus) is intended to analyze the environmental and financial impacts of one or more products, considering its supply chain, allowing to compare performance and formulate strategies for action. The research method employed has four phases: the first explores the literature underpinning the research evidence relevant to the proposed objective, the second phase proposes the array and method of work, the third phase implements the proposals in a real context of product development , the result of a project developed at the university to which the researcher is bound, this application enables the fourth stage, which analyzes the proposed method and discusses its results in the context where it was applied. The matrix presented is supported by three pillars: the environmental impac
Keywords: análise de ciclo de vida; sustentabilidade; matriz de posicionamento estratégico sustentável; life cycle assessment; sustainability; strategic positioning matrix sustainable; Engenharias